APLIKASI BELAJAR MEMBACA DAN MENGUCAPKAN HURUF HIJAIYAH UNTUK POCKET PC - Sobri, Muhammad (Universitas Bina Darma, 2012)
Progress of Science and Technology should be followed with the Iman and Takwa (IMTAK), unfortunately , if there are still many people who can not read the letters hijaiyah which is the basis of the Quran. Society has now been busy with various activitas so they are difficult to study with Ustad or Ustadza about hijaiyah letters. To overcome this problem the authors make an application using a Pocket PC because it is easy to use, easy to carry and facilitate the public in learning letters hijaiyah. Making this application the writer use waterfall method which consists of systems engineering, software requirements analysis, design, programming, testing, and maintenance, while the programming language using Microsoft Visual Basic.NET. With this application can help people who can not read the letters hijaiyah quickly and easily understood, because the application is equipped with a sound that existed at the pictures hijaiyah the letter. Keywords: VB.NET, Pocket PC